2009
DOI: 10.3182/20090901-3-ro-4009.00069
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Model and MIMO Control for Intelligent Buildings Temperature Regulation over WSN

Abstract: The aim of this paper is to propose a model-based feedback control strategy for indoor temperature regulation in buildings equipped with underfloor air distribution (UFAD). Supposing distributed sensing and actuation capabilities, a 0−D model of the ventilation process is first derived, based on the thermodynamics properties of the flow. A state-space description of the process is then inferred, including discrete events modeled by Markovian processes. This results in a hybrid model with nonlinear components. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…1, which consists of the electromechanical part (green box) and N building zones interconnected through doors and walls [Witrant et al (2009)]. The multi-zone HVAC system is regarded as a network of N + 1 interconnected subsystems Σ s , Σ (1) ,.…”
Section: Problem Formulationmentioning
confidence: 99%
“…1, which consists of the electromechanical part (green box) and N building zones interconnected through doors and walls [Witrant et al (2009)]. The multi-zone HVAC system is regarded as a network of N + 1 interconnected subsystems Σ s , Σ (1) ,.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Fig. 1 depicts the multi-zone HVAC system with the electromechanical part (green box) and the N building zones, which are interconnected through doors [10]. Let us consider the HVAC system as a network of N + 1 interconnected subsystems, where the subsystem associated with the water temperature dynamics in the storage tank is denoted by Σ s , and Σ (i) represents the subsystem associated with the i-th zone temperature dynamics, i ∈ N , where N = {1,...,N}.…”
Section: Problem Formulationmentioning
confidence: 99%
“…The coefficients a sz and a st (kJ/kg o C) represent the effectiveness of the heating coil and the heat loss of the storage tank due to exterior surfaces, respectively. Based on [8] and [10], the state space representation of the subsystem Σ (i) , i ∈ N , can be expressed as…”
Section: Problem Formulationmentioning
confidence: 99%
“…Studies related to the first and third item are found in, for example, [Camponogara et al, 2002, Speetjens et al, 2008, Witrant et al, 2009, Venkat et al, 2005. Though solutions on the third item of distributed control show promising results, they are currently limited to linear processes.…”
Section: Introductionmentioning
confidence: 99%